"Customer is king": Staging consumer culture in a food aid organization. (August 2022) - Andriessen, Thirza; Van der Horst, Hilje; Morrow, Oona
This paper intervenes in critical debates on the role of charitable food aid in meeting the material, social, emotional, and cultural needs of the people who depend on this aid. It offers a detailed case study of a social grocery in Belgium that attempts to circumvent the power inequalities and negative social and emotional impacts of charitable giving through staging consumer culture, and treating clients as customers. This is accomplished with supporting performances of consumption norms around product choice, the act of paying, and the selection of appropriate foods – which improves the ability of participants to meet their personal needs as well as the broader standards of consumer society that they are otherwise excluded from. These other ways of doing food aid are theorized through the lens of consumer culture, to explain what is at stake in performing the norms of market exchange in a consumer society.